Trends in sun-protection behaviour in Australian adults 2007-2012 - Koch, Severine; Pettigrew, Simone; Minto, C.; Slevin, T.; Strickland, M.; Lin, Chad; Jalleh, Geoffrey (2017)
BACKGROUND: Almost all skin cancers are the result of overexposure to UV radiation and could be prevented by adhering to a number of simple behavioural guidelines to minimise exposure to the sun. The present study examined trends in sun-protection behaviour among adults living in Western Australia, a region with high levels of UV radiation. METHODS: During five summers from 2008 to 2012, 2076 Western Australian adults participated in annual, cross-sectional telephone surveys that assessed how often they engaged in a range of sun-protection behaviour (seeking shade, staying inside and wearing a hat, protective clothing, sunscreen or sunglasses). RESULTS: Apart from an increase in sunscreen use and a consistently high use of sunglasses, most sun-protection behaviour remained stable at moderate levels during the 5-year period. Seeking shade, staying inside and wearing a hat were all practised at levels ranging between 'sometimes' and 'usually' on sunny days in summer during peak UV hours, with little to no variability across the survey years. Wearing protective clothing was the least frequent behaviour across all survey years and was significantly lower in the most recent survey year relative to baseline. CONCLUSIONS: Further efforts are required to encourage greater enactment of sun-protection behaviour, especially on the use of protective clothing and seeking shade during periods of high UV radiation.